Graphene oxide liquid crystals: a frontier 2D soft material for graphene-based functional materials. (16th July 2018) - Padmajan Sasikala, Suchithra; Lim, Joonwon; Kim, In Ho; Jung, Hong Ju; Yun, Taeyeong; Han, Tae Hee; Kim, Sang Ouk
Abstract : The discovery of graphene oxide liquid crystal (GOLC) has enabled a broad spectrum of novel graphene-based functional materials and triggered the development of other 2D-based liquid crystal systems. Abstract : Graphene, despite being the best known strong and electrical/thermal conductive material, has found limited success in practical applications, mostly due to difficulties in the formation of desired large-scale highly organized structures. Our discovery of a liquid crystalline phase formation in graphene oxide dispersion has enabled a broad spectrum of highly aligned graphene-based structures, including films, fibers, membranes, and mesoscale structures. In this review, the current understanding of the structure–property relationship of graphene oxide liquid crystals (GOLCs) is overviewed. Various synthetic methods and parameters that can be optimized for GOLC phase formation are highlighted. Along with the results from different characterization methods for the identification of the GOLC phases, the typical characteristics of different types of GOLC phases introduced so far, including nematic, lamellar and chiral phases, are carefully discussed. Finally, various interesting applications of GOLCs are outlined together with the future prospects for their further developments.